Waqf Management in Thailand: A Case Study in Bangkok Mosques - Orawit, Boonchom (2009)
Waqf properties in Thailand have been increasing since the presence of mosques in Thailand. However, the waqf is not managed in a convenient manner. Therefore, the aim of this study is to examine the form of waqf management, the situation of waqf management and the expression of waqf managers of mosques in waqf management. The study surveyed the Islamic committees of mosques via questionnaires and interviews. The results showed that the greatest form of waqf management in Thailand is the rental form. The key problem of waqf management is the lack of understanding of waqf management, and the key obstacle is waqf administrative law. The results of this study contribute to waqf management knowledge especially in terms of waqf management in non-Muslim countries. Furthermore, this study provides information in terms of the statistics on waqf, the function of waqf management in development and the economic significance of waqf management.